The Development of Augmented Reality Mobile Application: BrainARnatomy. - Noor Azman, Amirah Dayana; Che Dalim, Che Samihah (Applied Information Technology And Computer Science, 2023)
The brain is a powerful organ that manages thinking, memories, emotions,sensation, motor skills, vision, respiration, temperature, and hunger. Like other organs, the brain has various components that are each in charge of a certain function. The intricate folds and grooves enable different sections to connect and facilitate human behavior. Educating children about brain function can boost their confidence, although practical implementation remains pending. This proposal aims to create an augmented reality (AR) mobile app, BrainARnatomy, targeting 10-year-old children. Utilizing the Multimedia Mobile Content Development (MMCD) approach, this app will raise awareness about the brain, foster a growth mindset, and provide information about its different parts. This application is expected to be useful for providing background knowledge on the brain, growth mindset, and various parts of the brain.